INFLUENCE OF DEFECT IN THE CONCRETE PILES USING NON-DESTRUCTIVE TESTING - Mosa Al-Mosawe; Yousef Al-Shakarchi; A'amal A- Saidi (Journal of Engineering, 2006)
This paper presents the results of experimental investigation carried out on concrete model piles to study the behaviour of defective piles. This was achieved by employing non-destructive tests using ultrasonic waves. It was found that the reduction in pile stiffness factor is found to be about (26%) when the defect ratio increased from (5%) to (15%). The modulus of elasticity reduction factor as well as the dynamic modulus of elasticity reduction factor increase with the defect ratio.